2018
DOI: 10.1007/s00380-018-1218-1
|View full text |Cite|
|
Sign up to set email alerts
|

Association between plasma levels of PCSK9 and the presence of coronary artery disease in Japanese

Abstract: The ability of pro-protein convertase subtilisin/kexin type 9 (PCSK9) levels to predict the presence or severity of coronary artery disease (CAD) remains controversial. The purpose of this study was to investigate these associations. We enrolled 393 patients who were clinically suspected to have CAD or who had at least one cardiac risk factor and underwent multidetector-row computed tomography coronary angiography. The presence of CAD (≥50% coronary stenosis), the number of significantly stenosed coronary vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…The relationship of PCSK9, total or LDL cholesterol and Lipoprotein (a) has been demonstrated in many different populations and in large study cohorts [11, 3437]. On the other hand, the relationship of PCSK9 levels and HDL cholesterol is less well established, and a clear involvement of PCSK9 in HDL metabolism is indeed uncertain [12, 3842]. Interestingly, we found that the relationships of PCSK9 with LDL cholesterol was affected and, as matter of fact, obscured by statin treatment, while that with HDL cholesterol was not (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of PCSK9, total or LDL cholesterol and Lipoprotein (a) has been demonstrated in many different populations and in large study cohorts [11, 3437]. On the other hand, the relationship of PCSK9 levels and HDL cholesterol is less well established, and a clear involvement of PCSK9 in HDL metabolism is indeed uncertain [12, 3842]. Interestingly, we found that the relationships of PCSK9 with LDL cholesterol was affected and, as matter of fact, obscured by statin treatment, while that with HDL cholesterol was not (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The modi ed Gensini score is an reliable marker for assessing the severity of coronary artery disease. Some experts found that patients with severe CAD were grouped according to the modi ed Gensini score, and the results indicated that there were signi cant differences between the highly rated groups and other groups 35,36 . In our work, CHR was positively correlated with the modi ed Gensini score, suggesting that patients with relatively high CHR may have more severe coronary stenosis, and that CHR may be useful in predicting the severity of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…About 1,000 patients who were clinically suspected to have CAD and who underwent CCTA were included in the FU-CCTA Registry [11-21]. The number of significantly stenosed coronary vessels (VD, ≥ 50% coronary stenosis is diagnosed as CAD), and the Gensini score was quantified using CCTA.…”
Section: Fu-ccta Registrymentioning
confidence: 99%
“…(Table 1). Recently, we examined three Registries at Fukuoka University (FU) in Japan and identified risk factors for CVD for the primary and secondary prevention of atherosclerotic coronary artery disease (CAD): the Quantitative Coronary Angiography (FU-QCA) Registry [3-10], the Coronary Computed Tomography Angiography (FU-CCTA) Registry [11-21], and the Coronary Intravascular Ultrasound (FU-IVUS) Registry [22-27] (Table 2). Here, we review the problems that persist regarding the onset and progression of CVD independent of statin treatment based mainly on our data from these three Registries.…”
Section: Introductionmentioning
confidence: 99%